Prevalence of new Onset Right Bundle Branch Block in Acute Myocardial Infarction and its Coronary Angiographic Findings in Patients Attending NICVD - Asfandyar, Mati Ullah Khan, Muhmmad Umar Farooq, Saeed Maqsood, Muhammad Rehan Khan, Muhammad Ahsan Bashir (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Acute myocardial infarction patients with left and right bundle branch block significantly contributes to higher risk of mortality. Right bundle branch block (RBBB) has clinical implications in acute myocardial infarction setting. The present study aimed to determine the prevalence of new onset RBBB in acute myocardial infarction and its association with coronary angiographic findings. Methodology: This cross-sectional study was conducted on 82 acute myocardial infarction (AMI) patients in National Institute of Cardiovascular Diseases (NICVD), Karachi from January 2022 June 2022. Study protocol was approved from the institution research and ethical committee. All the patients of either gender with an age range 25 years to 85 years having acute myocardial infarction were included. Written informed consent was taken. Patients with previous RBBB, had implanted pacemaker, and presentation of symptoms >24 hours were excluded. Detailed history and clinical examination of each individual was done. Patients’ angiographic findings after eligibility based on coronary angiography was done and recorded. All the data were entered into pre-designed profroma. SPSS version 26 was used for data analysis. Results: Of the total 82 AMI patients, there were 48 (58.5%) male and 34 (41.5%) females. Age-wise distribution of AMI patients were as follows; 17 (20.7%) 25-45 years, 28 (34.2%) 46-65 years, and 37 (45.1%) 66-85 years. The overall mean age was 54.62±6.82 years. The prevalence of new onset RBBB and without RBBB was 17 (20.7%) and 65 (79.3%) respectively. Of the 17 AMI with RBBB patients, the incidence of single vessel disease, double vessel disease, triple vessel disease, and left main stem disease was 3 (17.6%), 5 (29.4%), 6 (35.3%) and 3 (17.6%) respectively. Majority of patients aged 46 years to 65 years had RBBB in 9 (32.1%), followed by 6 (16.2%) in patients 66-85 years and 2 (11.8%) in patients aged 25-45 years. Conclusion: The present study concluded that the prevalence of new onset RBBB was 20.7% among acute myocardial infarction patients. The incidence of triple vessel disease was prominent in acute myocardial infarction patients with RBBB followed by double vessel disease. Also, elderly patients of acute myocardial infarction patients were more susceptible to RBBB than younger one. Keywords: Right bundle branch blockage, Acute myocardial infarction, Coronary angiography